Relasi Kuasa dalam Kehidupan Politik Masyarakat Melayu Riau: Menemukan Penopang Demokrasi di Aras Lokal - Ishak (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2013)
Study of cultural values and political life of the community in Riau Malay, which is believed to beable to support the application of the principles of democracy at the local level. This is consideredimportant because of the values and culture that lives and grows a reflection of power relationsbetween individuals, groups, social institutions, and governments in the region that has lasted along time.Political system and democratic governance requires the participation of all citizens in thepolitical process is important. On this basis, the research interest in restoring the values andculture of the Malay community, which will be explored from theoretical perspectives - normativeand empirical, both in the kingdom, independence, and decentralization (regional autonomy)today, in order to understand the knowledge local power relations and their implications for thedemocratic process that relies on the framework and capabilities fikir society itself.In this research, emphasis will be devoted to the use of qualitative methods. The data analysistechnique used the descriptive analysis. As a non-statistical analysis techniques, in addition topresenting information and facts for what it is, a description and interpretation of the data, tables,graphs, or figures are available is also a typical sharpness of this method of analysis. Analysis willalso be preceded by exposition and explanation of empirical facts (deductive) that relate directlyto this study. In addition, empirical facts will also conceptualized with the theory which is thentested in a rational (inductive).